Perceived need and utilization of dental health care services in Indonesia: A secondary analysis using the national socioeconomic data - Malik, Normaliza Ab; Rosalien, Robbykha; Khalissya, Nadine; Badruddin, Iwany Amalliah; Maharani, Diah Ayu (UI Scholars Hub, 2020)
Background: Perceived needs and utilization of oral health services are important to ensure improvements in oral health outcomes and to allocate resources for the continuous provision of the services. This study aimed to determine the factors influencing the perceived needs and utilization of oral health services in Indonesia. Methods: Secondary data from the 2013 Indonesian National Socioeconomic Survey (n = 260,925) was used. Descriptive analysis and logistic regression were employed to describe the relationship between perceived needs and utilization of oral health services. Results: The proportions of Indonesians who had a perceived need for oral health services and utilized the services in 2013 were 1.64% and 2.30%, respectively. A higher probability of perceived need and utilization of dental health care services was observed in the respondents who wereold, females, unmarried, and living in rural areas and in those who had a higher level of education and health insurance. Conclusion: The proportions of individuals who presented with perceived needs and utilization of dental health care services were low and were associated with age, gender, marital status, geographic location, level of education, and insurance status. Appropriate strategies and policies are warranted to improve oral health in Indonesia.